The Impact Of Family Environment And Parenting Approaches On Child Health Development Outcomes - V, Dr. Atibha; G, Dr. Anbahazhagan; Madhumita, Dr. Paleri; Devadarshini P, Miraculine (Adolescência e Saúde, 2026)
Background: The health and development stages of children are sensitive to the family environment and parenting style. Positive parenting and a supportive home environment leads to ideal physical development, emotional well-being, and cognitive development whereas a poor environment can be a set-back to well-being. Objective: To determine the effects of family environment and parenting styles on child health and developmental outcome in children aged between 5-15 years. Methodology: An analytical study was followed on 300 parentchild pairs in a descriptive manner. Structured questionnaires on parenting style, family set up and child health metrics were used to gather data. The statistical analysis (correlation and regression analysis) was done using SPSS. Findings: Findings showed that 46% of the families depicted positive parenting and enabling conditions. These settings resulted in children with a higher rate of healthy growth (84%), reduced illness frequency (18%), and KM of higher emotional and cognitive score (88%). Family environment, parenting styles and child outcomes showed a significant association (p < 0.01). Conclusion: Effective parenting strategies and positive family environments are important contributors towards improving child health and development. The enhancement of the family support systems, as well as the encouragement of positive parenting practices, is crucial in augmenting the overall well-being of children.